2012
DOI: 10.3892/or.2012.1907
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the mitotic-arrest deficiency 2 is associated with chemotherapy resistance in ovarian serous adenocarcinoma

Abstract: Mitotic-arrest deficiency 2 (MAD2) is a key component of spindle assembly checkpoint (SAC) function; SAC mediates spindle microtubule attachment to kinetochores on chromosomes and chromosomal segregation during mitosis. To determine whether MAD2 expression is associated with chemotherapy resistance in ovarian serous adenocarcinoma, we reviewed tumor samples from 41 cases of ovarian serous adenocarcinoma at Osaka City University Medical School Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…CENPN is required to recruit the Mad2 SAC protein to prometaphase kinetochores [24]. MAD2 is a key component of the mitotic spindle checkpoint pathway, and MAD2 overexpression is observed in several cancers [25]. MAD2 overexpression in transgenic mice notably results in chromosomal instability and initiates carcinogenesis in a wide variety of tumors [26].…”
Section: Discussionmentioning
confidence: 99%
“…CENPN is required to recruit the Mad2 SAC protein to prometaphase kinetochores [24]. MAD2 is a key component of the mitotic spindle checkpoint pathway, and MAD2 overexpression is observed in several cancers [25]. MAD2 overexpression in transgenic mice notably results in chromosomal instability and initiates carcinogenesis in a wide variety of tumors [26].…”
Section: Discussionmentioning
confidence: 99%
“…BUBR1 and MAD2 directly prevent activation of the Anaphase-Promoting Complex (APC/c) by binding to CDC20 and maintaining a closed confirmation [210]. Using siRNA to silence MAD2, PTX-induced apoptosis was reduced and demonstrated that MAD2 levels play a definite role in the SAC signal, mitotic arrest, and arrest-induced apoptosis [211][212][213]. Moreover, decreased levels of MAD2 have even been hypothesized to be a factor in tumorigenesis in mucinous OC [214], suggesting that MAD2 is more of a driving factor in cell proliferation and disease progression than any other SAC-related protein.…”
Section: Spindle Assembly Checkpointmentioning
confidence: 99%
“…As a component of the mitotic checkpoint, high levels of MAD2L1 are related to increased cellular proliferation, migration, and metastasis, which can lead to shorter survival in various cancers [22][23][24][25][26]. However, in ovarian cancer, the role of MAD2L1 did not agree with previous findings that patients with lower MAD2L1 levels were less sensitive to paclitaxel and had shorter progression-free survival (PFS) and overall survival (OS) [27,28]. This discrepancy might have been caused by our analysis, ignoring the mutations of p53 and BRCA1, which are known regulators of MAD2L1 and are commonly mutated in HGSOC [29,30].…”
Section: Discussionmentioning
confidence: 85%